Acoustic Front Ends for Speaker-Independent Digit Recognition in Car Environments - Langmann, Detlev; Fischer, Alexander; Wuppermann, Friedhelm; Haeb-Umbach, Reinhold; Eisele, Thomas (Eurospeech)
This paper describes speaker-independent speech recognition experiments concerning acoustic front end processing on a speech database that was recorded in 3 different cars. We investigate different feature analysis approaches (mel-filter bank, mel-cepstrum, perceptually linear predictive coding) and present results with noise compensation techniques based on spectral subtraction. Although the methods employed lead to considerable error rate reduction the error analysis shows that low signal-to-noise ratios are still a problem